Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine the pair of functions [tex]\( f(a) \)[/tex] and [tex]\( g(x) \)[/tex] such that the composition [tex]\( (g \circ f)(a) = |a| - 2 \)[/tex], we can break down the problem step-by-step.
1. Assume a function [tex]\( f(a) \)[/tex]: Let's consider the function [tex]\( f(a) \)[/tex] to be the absolute value function, i.e., [tex]\( f(a) = |a| \)[/tex].
2. Define [tex]\( g(x) \)[/tex]: We need to find [tex]\( g(x) \)[/tex] such that when we apply [tex]\( g \)[/tex] to [tex]\( f(a) \)[/tex], the result is [tex]\( |a| - 2 \)[/tex]. Since [tex]\( f(a) \)[/tex] is equal to [tex]\( |a| \)[/tex], we need [tex]\( g \)[/tex] to reduce [tex]\( |a| \)[/tex] by 2. Therefore, we can define [tex]\( g(x) \)[/tex] as [tex]\( g(x) = x - 2 \)[/tex].
To verify, let's see how these functions work together.
- For a given [tex]\( a \)[/tex], first apply [tex]\( f \)[/tex]:
[tex]\[ f(a) = |a| \][/tex]
- Then apply [tex]\( g \)[/tex]:
[tex]\[ g(f(a)) = g(|a|) = |a| - 2 \][/tex]
Thus, the pair of functions [tex]\( f(a) = |a| \)[/tex] and [tex]\( g(x) = x - 2 \)[/tex] indeed satisfies the condition [tex]\( (g \circ f)(a) = |a| - 2 \)[/tex].
Let's check this with an example:
- Let [tex]\( a = -5 \)[/tex]:
- [tex]\( f(a) = |-5| = 5 \)[/tex]
- [tex]\( g(f(a)) = g(5) = 5 - 2 = 3 \)[/tex]
The result matches [tex]\( |a| - 2 \)[/tex] because [tex]\( |-5| - 2 = 5 - 2 = 3 \)[/tex].
Thus, the functions are:
[tex]\[ f(a) = |a| \][/tex]
[tex]\[ g(x) = x - 2 \][/tex]
1. Assume a function [tex]\( f(a) \)[/tex]: Let's consider the function [tex]\( f(a) \)[/tex] to be the absolute value function, i.e., [tex]\( f(a) = |a| \)[/tex].
2. Define [tex]\( g(x) \)[/tex]: We need to find [tex]\( g(x) \)[/tex] such that when we apply [tex]\( g \)[/tex] to [tex]\( f(a) \)[/tex], the result is [tex]\( |a| - 2 \)[/tex]. Since [tex]\( f(a) \)[/tex] is equal to [tex]\( |a| \)[/tex], we need [tex]\( g \)[/tex] to reduce [tex]\( |a| \)[/tex] by 2. Therefore, we can define [tex]\( g(x) \)[/tex] as [tex]\( g(x) = x - 2 \)[/tex].
To verify, let's see how these functions work together.
- For a given [tex]\( a \)[/tex], first apply [tex]\( f \)[/tex]:
[tex]\[ f(a) = |a| \][/tex]
- Then apply [tex]\( g \)[/tex]:
[tex]\[ g(f(a)) = g(|a|) = |a| - 2 \][/tex]
Thus, the pair of functions [tex]\( f(a) = |a| \)[/tex] and [tex]\( g(x) = x - 2 \)[/tex] indeed satisfies the condition [tex]\( (g \circ f)(a) = |a| - 2 \)[/tex].
Let's check this with an example:
- Let [tex]\( a = -5 \)[/tex]:
- [tex]\( f(a) = |-5| = 5 \)[/tex]
- [tex]\( g(f(a)) = g(5) = 5 - 2 = 3 \)[/tex]
The result matches [tex]\( |a| - 2 \)[/tex] because [tex]\( |-5| - 2 = 5 - 2 = 3 \)[/tex].
Thus, the functions are:
[tex]\[ f(a) = |a| \][/tex]
[tex]\[ g(x) = x - 2 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.